50‐1: Invited Paper: Designs and Manufacturing Processes for microLED Displays in Handsets, Smartwatches, and Personal Computers. Issue 1 (28th June 2022) - Meitl, M. A.; Ozbas, M.; Knausz, I.; Fox, S.; Pearson, A.; Jain, N.; Radauscher, E.; Bonafede, S.; Meyer, C.; Verreen, C.; Lynch, J.; Keller, B.; et al.
Abstract : Industry‐wide efforts to develop microLED technology for displays brought focused attention to the importance of mass transfer micro‐assembly. Processes that are compatible with high‐volume manufacturing that can rapidly manipulate millions of discrete micron‐scale semiconductor objects per product unit are a new technological capability and required for making microLED displays accessible to mainstream consumer applications. As those assembly processes become mature, new attention shifts to the microLED devices themselves and to electronic driving schemes to operate them. Furthermore, mature mass transfer processes make possible new semiconductor constituents to the backplane, including singlecrystal devices with levels of integration density that are not natively available to display panel manufacturing. This confluence of new requirements and new possibilities sets a stage for far‐reaching innovation in consumer displays. This paper describes designs for microLED displays that use micron‐scale full color emitter packages and micron‐scale driver elements (microICs) that control clusters of pixels. A combination of mass transfer and conventional backplane fabrication processes is suitable for making displays of these designs, and the resulting products will support more than 300‐400 pixels per inch with advantageous power consumption characteristics.